Evaluation of flash dried yeast as a nutritional supplement in plant‐based practical diets for Pacific white shrimp Litopenaeus vannamei. (8th February 2017) - Qiu, X.; Davis, D.A.
Abstract: Growth and digestibility trials were conducted to evaluate the use of flash dried yeast (FDY) as a supplement in practical shrimp feeds. The six‐week growth trial evaluated the effects of FDY supplementation (0, 10, 20, 40 and 60 g kg –1 ) in the plant‐based practical diet on the performances and proximate compositions of juvenile Pacific white shrimp, Litopenaeus vannamei . Final biomass, final mean weight, per cent weight gain (WG), feed conversion (FCR) and protein retention efficiency (PRE) of Pacific white shrimp were not significantly influenced when FDY was added up to 40 g kg –1 of the diet. However, 60 g kg –1 FDY supplementation significantly reduced growth, feed utilization and protein retention. Supplementation of FDY in the practical diets of Pacific white shrimp did not affect protein, moisture, lipid, crude fibre, and ash content of whole shrimp body. Apparent digestibility coefficients of energy, protein, and amino acid (AA) for FDY were determined using chromic oxide as an inert marker and the 70:30 replacement technique. The energy and protein digestibility of FDY were 38.20% and 53.47%, respectively, which were significantly lower than fishmeal (FM) and soybean meal (SBM) that were run at the same time. Most amino acid digestibility of FDY was lowest among the three ingredients tested. Results of this work indicated that energy, protein and amino acid digestibility of FDY are lower compared to SBM and FM, and high levels supplementation (≥60 g kg –1 ) of FDY can cause negative effects to the growth response of Pacific white shrimp. Based on these results, further research regarding the effects of the low level inclusion of FDY in practical diets on immune responses of Pacific white shrimp is warranted.